Black heat [videorecording (DVD)] - Mitchell, Jason, 1987-; DreamDoll, 1992-; NLE Choppa, 2002-; Hendricks, Garrett (Dark Star Pictures, 2025)
The high stakes action thriller follows two determined parents who venture into a dark and ruthless underworld to rescue their teen daughter. Fueled by love they must take justice into their own hands, igniting a powder keg of revenge and resilience.